Tadpole of Microhyla picta Shenkel (Anura: Microhylidae), an endemic narrow-mouthed frog from Vietnam - Vassilieva, Anna B.; Trounov, Vitaly L. (Zootaxa, 2018)
The Painted Rice Frog, Microhyla picta Schenkel, is one of the least studied species among narrow-mouthed frogs of the genus Microhyla. To date it is known only from Vietnam, where it is distributed mostly in eastern coastal areas in central and southern parts of the country (Nguyen et al. 2009; Nguyen & Hoang 2013). The species was also found in Con Dao archipelago (Poyarkov & Vassilieva 2011). No data are available on the ecology and reproductive biology of the species, and its larval morphology is also not described. Microhyla frogs are widespread and numerous in terrestrial ecosystems and microhylid tadpoles are known to play an important role in the aquatic communities of temporary waterbodies of monsoon ecosystems in Southeast Asia (Heyer 1973; Vassilieva et al. 2017). The ability to identify microhylid tadpoles in the field is pertinent for biodiversity and ecological studies. We provide a description of larvae of M. picta from various areas in southern Vietnam.